PHENOL-2-(1-METHYL ETHOXY)-METHYL CARBAMATE COUMPOUND IN ETHYL ACETATE EXTRACT OF STEM BARK OF Aglaia angustifolia - Sofnie M. Chairul (Indonesian Journal of Chemistry, 2008)
Isolation of carbamate coumpound from ethyl acetate extract of stem bark of Aglaia angustifolia (Meliaceae), was carried out. The dried stem bark of A. angustifolia was extracted with ethanol (polar solvent), ethyl acetate (medium of polar) and water. From there extract solvent was biological activity test to Crocidolomia binotallis. Ethyl acetate extract solvent more active than another solvent, so that this extract was fractioned and clean up using chromatograpgy column, use SiO2 as stationary phase, mixture of n-hexane/ethyl acetate (10:1 ~ 1:1), ethyl acetate, and ethanol respectively as elution solution. The result of Biological activity test to C. binotallis showed that fraction of ethyl acetate inhibited growth on LC50 3.57 ppm. The compound of isolation result using HPLC, GCMS, FTIR and NMR was identified as phenol-2(1-methyl ethoxy) methyl carbamate coumpound, active as botanical insecticide.